Reliability of Anaerobic Contributions during a Single Exhaustive Knee-extensor Exercise - Luches-Pereira, Gabriel; Kalva-Filho, Carlos Augusto [UNESP]; Bertucci, Danilo Rodrigues; de Carvalho, Carlos Dellavechia; Barbieri, Ricardo Augusto; Papoti, Marcelo (Thieme, 2024)
The total anaerobic contribution (AC[La-] + PCr) is a valid and reliable methodology. However, the active muscle mass plays an important role in the AC[La-] + PCr determination, which might influence its reliability. Thus, this study aimed to investigate the effects of two exhaustive intensities on the reliability of the AC[La-] + PCr during a one-legged knee extension (1L-KE) exercise. Thirteen physically active males were submitted to a graded exercise to determine the peak power output (PPO) in the 1L-KE. Then, two constant-load exercises were conducted to task failure at 100 % (TTF100) and 110 % (TTF110) of PPO, and the exercises were repeated on a third day. The blood lactate accumulation and the oxygen uptake after exercise were used to estimate the anaerobic lactic and alactic contributions, respectively. Higher values of AC[La-] + PCr were found after the TTF100 compared to TTF110 (p = 0.042). In addition, no significant differences (p = 0.432), low systematic error (80.9 mL), and a significant ICC (0.71; p = 0.004) were found for AC[La-] + PCr in the TTF100. However, an elevated coefficient of variation was found (13.7 %). In conclusion, we suggest the use of the exhaustive efforts performed at 100 % of the PPO with the 1L-KE model, but its elevated individual variability must be carefully considered in future studies.
Keywords: anaerobic metabolism; high-intensity effort; MAOD; performance; reliability